2018
DOI: 10.1002/berj.3476
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive achievement of children of immigrants: Evidence from the Millennium Cohort Study and the 1970 British Cohort Study

Abstract: Although numerous studies have described the educational attainment of ethnic minorities in the UK, few have focused specifically on children born in the UK to two immigrant parents. First, using ordinary least squares (OLS) estimation, this article examines the cognitive assessment scores of children of immigrants in the 1970 British Cohort Study (BCS70) and the Millennium Cohort Study (MCS). It then exploits the richer data of the MCS to construct multilevel models for children of immigrants in this more rec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
1
12
0
1
Order By: Relevance
“…Lastly, we do not know if achievement varies by age. Previous work has shown that disparities for children of immigrants may be greatest at younger ages (Hoffmann 2018), and educational parity at older ages may not translate to equality in the labor market (Lee 2021:192-93). Future work should investigate achievement at younger ages as well as the school-to-work transition for the 0.5 generation.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we do not know if achievement varies by age. Previous work has shown that disparities for children of immigrants may be greatest at younger ages (Hoffmann 2018), and educational parity at older ages may not translate to equality in the labor market (Lee 2021:192-93). Future work should investigate achievement at younger ages as well as the school-to-work transition for the 0.5 generation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence that racial discrimination is linked to lower achievement (Archer, 2003), groups with higher likelihood of discrimination in fact do better in verbal scores over time, according to this model. This may have something to do with the generally high levels of academic achievement of ethnic minorities in the United Kingdom at older ages (Hoffmann, 2018). Shah et al (2010) suggest that ethnic minority families see education as a more sure path of social mobility in a society that places them at structural risk of discrimination; this positive slope value may represent such agentic resistance to discriminatory barriers.…”
Section: Discussionmentioning
confidence: 99%
“…In education, some studies have shown achievement gaps for pupils identifying as Black Caribbean (Coard, 1971;Gillborn, 2008;Strand, 2012), Pakistani, and Bangladeshi (DfES, 2006;Gillborn & Mirza, 2000). Other studies show that these gaps narrow or become insignificant by adolescence, at least in models with statistical controls (Hoffmann, 2018;Strand et al, 2015). In addition, Indian and Chinese children of immigrants might even exceed the educational outcomes of other children (Archer & Francis, 2007;DfES, 2006;Hoffmann, 2018).…”
Section: Children Of Immigrants In the Ukmentioning
confidence: 96%
See 2 more Smart Citations